Recruiting diversity where it exists: The Alabama Genomic Health Initiative. Issue 3 (27th March 2020) - May, Thomas; Cannon, Ashley; Moss, Irene P.; Nakano‐Okuno, Mariko; Hardy, Sharonda; Miskell, Edrika L.; Kelley, Whitley V.; Curry, William; East, Kelly M.; Acemgil, Aras; Schach, Julie; Sodeke, Stephen O.; et al.
Abstract: Lack of diversity among genomic research participants results in disparities in benefits from genetic testing. To address this, the Alabama Genomic Health Initiative employed community engagement strategies to recruit diverse populations where they lived. In this paper, we describe our engagement techniques and recruitment strategies, which resulted in significant improvement in representation of African American participants. While African American participation has not reached the representation of this community as a percentage of Alabama's overall population (26%–27%), we have achieved an overall representation exceeding 20% for African Americans. We believe this demonstrates the value of engagement and recruitment where diverse populations reside.